2017
DOI: 10.1093/eurheartj/ehx504.3874
|View full text |Cite
|
Sign up to set email alerts
|

3874Implantable cardiac defibrillator in the setting of tetralogy of fallot: data from the DAI-T4F National Registry

Abstract: Risk prediction for sudden cardiac death and ICD treatments 815(11.7 million inhabitants) between 2006 and 2010, we identified characteristics associated with an increased risk of pre-hospital SCD and used these variables to build a SCD prediction score which we validated internally and externally. Results: In the overall STEMI population, (n=8112; median age 60 years, 78% males), SCD occurred in 452 patients (5.6%). By multivariate analysis, younger age, absence of obesity, absence of diabetes, shortness of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The DAI-T4F National Registry of all TOF subjects implanted with an ICD between 2005 and 2016 showed that ≥ 1 complication occurred in 40 patients (39%), including inappropriate shock (n = 26), major pocket hematoma (n = 1), lead dysfunction (n = 15), infection (n = 6), reflex sympathetic dystrophy (n = 2), and device failure needing reintervention (n = 3). 8 Our patient also experienced lead dysfunction, which is a known complication; however, unilateral breast enlargement has not previously been reported.…”
Section: Discussionmentioning
confidence: 54%
“…The DAI-T4F National Registry of all TOF subjects implanted with an ICD between 2005 and 2016 showed that ≥ 1 complication occurred in 40 patients (39%), including inappropriate shock (n = 26), major pocket hematoma (n = 1), lead dysfunction (n = 15), infection (n = 6), reflex sympathetic dystrophy (n = 2), and device failure needing reintervention (n = 3). 8 Our patient also experienced lead dysfunction, which is a known complication; however, unilateral breast enlargement has not previously been reported.…”
Section: Discussionmentioning
confidence: 54%